Overview of tar reduction in biomass-derived producer gas using non-thermal plasma discharges - Kittikorn Sasujit (2019)
© 2019 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. Non-thermal plasma is defined as a partially ionised gas where free electrons attain high energy levels and high temperature but where neutral particles and ions carry negligible energy, and the overall temperature of the bulk gas remains low. Non-thermal plasma discharges have been widely applied in various areas such as surface modification, gas discharge lamps, low-temperature plasma chemistry, and pollutant abatement. This work investigates the potential of non-thermal plasma in the treatment of tar. In addition, an overview of recent development in the removal of tar from biomass-derived producer gas is presented with a focus on non-thermal plasma utilisation. The background of tar and non-thermal plasma technology is described and followed by up-to-date progress in applying non-thermal plasma to tar destruction. The effects of the input power and input tar concentration on the destruction efficiency, energy efficiency and gas composition are presented and the performance of several plasma systems is compared and discussed.